2019
DOI: 10.1111/jdv.15454
|View full text |Cite
|
Sign up to set email alerts
|

Early outcome of a 31‐gene expression profile test in 86 AJCC stage IBII melanoma patients. A prospective multicentre cohort study

Abstract: Background The clinical and pathological features of primary melanoma are not sufficiently sensitive to accurately predict which patients are at a greater risk of relapse. Recently, a 31‐gene expression profile (DecisionDx‐Melanoma) test has shown promising results. Objectives To evaluate the early prognostic performance of a genetic signature in a multicentre prospectively evaluated cohort. Methods Inclusion of patients with AJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 27 publications
1
44
0
Order By: Relevance
“…The 31-GEP test further stratified patients with negative SLNB for distant metastatic risk. Similarly, two recent prospective studies (consisting primarily of AJCC stage I/II patients) found GEP class to be the strongest predictor of both local recurrence and distant metastasis [8,9]. Finally, in a study of 1421 prospectively tested T1/T2 tumor stage patients – most undergoing SLNB – from 26 centers, GEP class was a significant predictor of SLNB-positivity [10].…”
Section: Prognostic Gep Tests For Melanomamentioning
confidence: 96%
“…The 31-GEP test further stratified patients with negative SLNB for distant metastatic risk. Similarly, two recent prospective studies (consisting primarily of AJCC stage I/II patients) found GEP class to be the strongest predictor of both local recurrence and distant metastasis [8,9]. Finally, in a study of 1421 prospectively tested T1/T2 tumor stage patients – most undergoing SLNB – from 26 centers, GEP class was a significant predictor of SLNB-positivity [10].…”
Section: Prognostic Gep Tests For Melanomamentioning
confidence: 96%
“…Analytically, this gene expression profile (GEP) has demonstrated reproducibility across instruments in separating "class 1" (low-risk) from "class 2" (high-risk) probability scores and in technical concordance between runs (82). Results from small retrospective and prospective clinical cohorts have suggested improved ability to stratify risk of relapse and distant metastasis independent of SLNB status (83)(84)(85)(86)(87). However, each of these studies are limited by the lack of stage or substage breakdown of test performance, rendering it difficult to determine how much additional information is imparted by the biomarker beyond existing staging criteria.…”
Section: Prognostic Biomarkersmentioning
confidence: 99%
“…However, each of these studies are limited by the lack of stage or substage breakdown of test performance, rendering it difficult to determine how much additional information is imparted by the biomarker beyond existing staging criteria. Podlipnik et al studied the additive utility of DecisionDx probability scores in conjunction with combined AJCC stages ("low-risk": IB-IIA, "high-risk": IIB-IIC) and found disease free survival was lower in melanoma patients with DecisionDx high-risk "class 2" scores, regardless of grouped AJCC staging (87). Furthermore, in a 205 patient cohort, comprised of combined Stage I and II melanoma cases, where the DecisionDx GEP was combined with the AJCC Individualized Melanoma Patient Outcome Prediction Tool, the authors reported improved sensitivity but worse specificity for predicting disease recurrence, distant metastasis, and death compared to either metric alone (78).…”
Section: Prognostic Biomarkersmentioning
confidence: 99%
“…The 31-GEP seeks to identify those T1 and T2 tumors with genetic signatures that are likely to behave in either low-risk or high-risk manners with regard to recurrence, distant metastasis, and mortality. 6,8-11 This test stratified patients into 4 groups: Class 1A (considered low risk of metastasis or recurrence), Classes 1B and 2A (intermediate risk), and Class 2B (high risk). When these groups are further broken down by patient age, it becomes apparent that patients >55 years of age whose tumors are Class 1A have <5% incidence of SLNB positivity.…”
Section: Introductionmentioning
confidence: 99%